Multiproxy approach to reconstruct fossil primate feeding behavior: Case study for macaque from the Plio-Pleistocene site Guefaït-4.2 (eastern Morocco) - Ramírez-Pedraza, Iván; Martínez, Laura M.; Aouraghe, Hassan; Rivals, Florent; Tornero, Carlos; Haddoumi, Hamid; Estebaranz-Sánchez, Ferran; Rodríguez-Hidalgo, Antonio; van der Made, Jan; Oujaa, Aïcha; Ibáñez, Juan José; Mhamdi, Hicham; et al. (Frontiers in Ecology and Evolution, 2023)
The genus Macaca belongs to Cercopithecidae (Old World monkeys), Cercopithecinae, Papionini. The presence of Macaca in North Africa is well known from the Late Miocene to the Late Pleistocene. However, the diet of fossil Macaca has been poorly described in the literature. In this study, we investigated the feeding habits of Macaca cf. sylvanus (n = 4) from the Plio-Pleistocene site Guefaït-4.2 in eastern Morocco through multiproxy analysis combining analyses of stable carbon and oxygen isotopes from tooth enamel, buccal microwear, and low-magnification occlusal dental microwear. For both microwear analyses, we compared the macaques with a new reference collection of extant members of Cercopithecoidea. Our results show for the fossil macaque a microwear pattern similar to the extant Mandrillus sphinx, Cercocebus atys, and Lophocebus albigena, African forest-dwelling species that are characterized by a durophagous diet based mainly on hard fruit and seed intake. Along the same lines, the δ13C of M. cf. sylvanus indicates a C3 based-diet without the presence of C4 plants typical of the savanna grassland in eastern Africa during this period. The high δ18O values of M. cf. sylvanus compared with the contemporary ungulates recovered from Guefaït-4.2 may be related to leaf and fruit consumption. The complementarity of these methods allows for a dietary reconstruction covering a large part of the individual’s life